Globalization and non-traditional security in South Asia - Khan, Abdur Rob.; Regional Centre for Strategic Studies (Colombo, Sri Lanka) (Dhaka : Academic Press and Publisher for Regional Centre for Strategic Studies, Colombo, 2001)
Contributed articles.
Includes bibliographical references and index.
Keywords: South Asia -- Foreign economic relations; South Asia -- Economic conditions; South Asia -- Social conditions